Methodology application for testing of the dapard information system for quality assurance processes - Agudelo Arboleda, Andrés; García Arango, David Alberto; Castro Ramírez, Frey de Jesús; Agudelo Arboleda, Andrés; García Arango, David Alberto; Castro Ramírez, Frey de Jesús; Agudelo Arboleda, Andrés; García Arango, David Alberto; Castro Ramírez, Frey de Jesús (Corporación universitaria Americana, 2022)
The development of an information system is presented that has a functional module that is the registration of events, consultation and integration of all kinds of information such as historical documentary geographic, (matrix tables among others) of disasters that occur throughout Antioquia but It should be considered that this system does not have information security systems, therefore, the application of a methodology that allows quality assurance is identified for the migration of databases since this information is not well structured which makes traceability difficult. It is proposed as final elements that it is important to have security implementation protocols in the platform that is managed there, which also requires being more intuitive for the user.